2012
DOI: 10.1002/ijc.27397
|View full text |Cite
|
Sign up to set email alerts
|

Race and prevalence of human papillomavirus infection among men residing in Brazil, Mexico and the United States

Abstract: HPV causes anal, penile and oropharyngeal cancers in men. Genital HPV prevalence in men appears to vary by world region with men residing in Asia having among the lowest prevalence. Unfortunately, there is little information on prevalence of HPV infection in men by race. The purpose of this study was to examine HPV prevalence by race across three countries. 3,909 men ages 18–70 years enrolled in an ongoing prospective cohort study of the natural history of HPV in men (The HIM Study) were included in the analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…Previous studies have reported a low prevalence of HPV infection among Asians in Continental Asia (17, 18) and we have shown racial differences in the prevalence of HPV [6] that persisted after adjustment for potential confounding and sexual behavior factors. Specifically, Asian/PI had the lowest HPV prevalence (42.2%) compared to Blacks (66.2%) and Whites (71.5%) and Asian/PI race was associated with a reduced risk HPV infection in multivariable analysis (prevalence ratio=0.65; 95% CI 0.52–0.80).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Previous studies have reported a low prevalence of HPV infection among Asians in Continental Asia (17, 18) and we have shown racial differences in the prevalence of HPV [6] that persisted after adjustment for potential confounding and sexual behavior factors. Specifically, Asian/PI had the lowest HPV prevalence (42.2%) compared to Blacks (66.2%) and Whites (71.5%) and Asian/PI race was associated with a reduced risk HPV infection in multivariable analysis (prevalence ratio=0.65; 95% CI 0.52–0.80).…”
Section: Discussionsupporting
confidence: 50%
“…Prevalence of genital HPV infection in men appears to vary by world region and to date there is little information on the acquisition (incidence) and persistence (clearance) of HPV infection in men by race. In a previous report [6] we assessed prevalence of HPV infection by race and observed the lowest HPV prevalence among Asian/Pacific Islanders (PI) even after adjusting for potential confounding factors. Our previous findings were consistent with previous studies that reported a lower prevalence of HPV infection among Asians in Continental Asia [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of genital HPV infection in men have examined only α-HPV types; the distribution of other HPV types present at the male genitals remains unknown. In the HIM study (Giuliano et al, 2008), over 66% of men tested positive for HPV at their first study visit; however, the viral type could not be identified in nearly 22% of these men (e.g., HPV PCR positive, no genotype specified) (Akogbe et al, 2012). Understanding the natural history of HPV infection in men is essential to better understand the transmission of these viruses and to study HPV related disease.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the exclusion of HPV ensured that the study assessed risky behaviour associated with general STI prevalence, rather than HPV prevalence (which has previously been published as part of the parent study). [21][22][23] Statistical analysis Since all variables were categorical, differences in the distribution of demographic characteristics and sexual behaviours were examined by age cohort and tested using the Chi square (χ 2 ) test. Logistic regression was conducted to examine the association between demographic factors and sexual behaviours and the likelihood of testing positive for an STI.…”
Section: Variablesmentioning
confidence: 99%